2011
DOI: 10.1017/s0007114511005642
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blackcurrant-based juice on atherosclerosis-related biomarkers in cultured macrophages and in human subjects after consumption of a high-energy meal

Abstract: Regular consumption of fruit and vegetables may be associated with decreased CVD risk. In the present study, we investigated the effects of blackcurrant (BC) juice, rich in polyphenols and ascorbic acid, on oxidative and inflammatory biomarkers in cultured macrophages in vitro and in human subjects with an atherosclerosis-prone phenotype (after consumption of a high-energy meal). In cultured macrophages (RAW264.7), BC treatment significantly inhibited lipopolysaccharide-induced inflammation as indicated by low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 46 publications
2
53
0
1
Order By: Relevance
“…After detailed analysis of the full text, 113 articles were rejected, due to lack of relevant outcomes, aspects of the study design, etc. Finally, 128 human RCTs published between March 1995 and March 2016 (included) [34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,…”
Section: Resultsmentioning
confidence: 99%
“…After detailed analysis of the full text, 113 articles were rejected, due to lack of relevant outcomes, aspects of the study design, etc. Finally, 128 human RCTs published between March 1995 and March 2016 (included) [34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,…”
Section: Resultsmentioning
confidence: 99%
“…Bilberries (vaccinuim myrtillus) and blackcurrants (ribes nigrum) are food sources that are particularly rich in bioavailable anthocyanins and flavonols [6,7]. Moreover, the relative antioxidant activity of anthocyanins and flavonols in bilberries and blackcurrants is especially high [8] and several studies have demonstrated beneficial effects of these berries on antioxidant status and low-grade inflammation [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Although spinach and broccoli are rich in antioxidants such as -tocopherol and carotenoids, the changes in neither PON1 lactonase nor arylesterase activity differed between the mixed meal with vegetables (SMFV meal) and that without vegetables (SMF meal) in this study. Therefore, changes in PON1 activity with the consumption of vegetables following ordinary meals may not occur in the postprandial state, as was in case of a study with blackcurrant juice, which is rich in water-soluble antioxidant polyphenols and ascorbic acid 26) . On the other hand, prior reports on human studies have shown that the intake of antioxidants exerts beneficial effects on PON1 activity [27][28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%